Assessing the structural stability of gluten-free snacks with different dietary fiber contents from adsorption isotherms. (November 2016) - Hoyos-Leyva, J.D.; Agama-Acevedo, E.; Bello-Perez, L.A.; Vernon-Carter, E.J.; Alvarez-Ramirez, J.
Abstract: Gluten-free snacks (GFS) with high dietary fiber and relatively low-fat contents were made by combining unripe plantain:chickpea:maize flours in the following proportions 50:30:0; 10:60:30; and 33:33:34, respectively. The adsorption isotherms built from equilibrium moisture content data of the snacks exposed to water activity (aw  = 0.10–0.90) at different temperatures (20, 25, 30, 35, 40, or 45 °C) environments, using a dynamic vapor sorption analyzer, were compared to those of a commercial snack control with high-fat content (33.85 g/100 g). All the snacks reached equilibrium moisture content within 5 h for most values of a w, and the experimental data were fitted with the Guggenheim-Anderson-de Boer model. The monolayer moisture content and the critical water activity (linked to glassy-to-rubbery phase transitions) of the GFS were significantly lower than that of the commercial snack, indicative that GFS underwent structural weakening under humidity stress. Also, the GFS showed a crossover in the isosteric heat of adsorption (estimated with Clausius-Clayperon equation) at approx. 11% relative moisture content that could be related to the formation of complex multilayered structures. The differences in the adsorption characteristics between GFS and commercial snack can be attributed to the chemical composition, mainly to the fat content. Highlights: Gluten-free snacks with high dietary fiber were formulated. Adsorption isotherms at different temperatures were obtained. Fat fraction had a large effect in monolayer moisture content. The higher the fat content, the smaller the critical water activity.